2006
DOI: 10.1099/jmm.0.46588-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antifungal treatment on the prevalence of yeasts in HIV-infected subjects

Abstract: Oral candidiasis, the most common opportunistic infection in patients with HIV infection, is usually associated with Candida albicans. Several factors may influence the carriage of Candida, including immunocompromised conditions and HIV infection, colonization by yeasts from different geographical areas and antimycotic treatment. This study investigated the Candida carrier rate, level and types of yeast in HIV-positive and -negative subjects, and the effect of previous exposure to antifungal drugs on the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 47 publications
7
27
1
1
Order By: Relevance
“…The candida carriage rate of the HIV+ patients in our study (61.4%) was comparable to that of other studies reporting carriage rates of 54.8–81.3% (Teanpaisan and Nittayananta, 1998; Tsang and Samaranayake, 2000; Campisi et al , 2002; Patel et al , 2006). The CD4 + cell count is commonly used as a marker for immunosuppression and disease progression in HIV‐infected patients.…”
Section: Discussionsupporting
confidence: 87%
“…The candida carriage rate of the HIV+ patients in our study (61.4%) was comparable to that of other studies reporting carriage rates of 54.8–81.3% (Teanpaisan and Nittayananta, 1998; Tsang and Samaranayake, 2000; Campisi et al , 2002; Patel et al , 2006). The CD4 + cell count is commonly used as a marker for immunosuppression and disease progression in HIV‐infected patients.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of yeast colonization in the mouth has differed widely depending on the age, location and immune status of the population sampled. A prevalence of 80 % was found in human immunodeficiency virus (HIV)-positive children compared with 57.5 % in their seronegative siblings (Cerqueira et al, 2010) A previous study in our hospital found a prevalence of 81.3 % in HIV-positive adults compared with 63 % in their HIV-negative counterparts (Patel et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Data from a previous study carried out in the same department (Patel et al, 2006) and in a similar group of patients attending the same HIV clinic before ARV therapy was introduced were extracted and compared with the present data. The same protocols were adopted, although the time and sample sizes were different.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the use of products from vegetal origin with potential antimicrobial activity can acquire meaning in therapeutical treatments (26, 39). The medicinal plants are frequently used in the treatment of some illnesses and, recently, have been intensely studied as alternative agents for the prevention of diseases, as oral diseases (38).…”
Section: Introductionmentioning
confidence: 99%